2019
DOI: 10.1213/ane.0000000000004207
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Safety and Efficacy of Sugammadex Versus Neostigmine for the Reversal of Neuromuscular Blockade in Children

Abstract: BACKGROUND: Sugammadex, with its novel mechanism of action of encapsulation and noncompetitive binding of aminosteroid neuromuscular-blocking agents (rocuronium and vecuronium), may offer distinct advantage to pediatric patients where residual neuromuscular blockade may be poorly tolerated. Data describing its use in the pediatric population are limited, and no large-scale studies are available evaluating the occurrence of adverse event across the full spectrum of ages. We sought to measure the occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 13 publications
3
25
2
Order By: Relevance
“…This implies that NMB has a sedative effect by decreasing afferent input and subsequent stimulation of brain arousal centers [19][20]. Tracheal extubation time was de ned as the time between study drug administration to extubation, which was much shorter in the sugammadex group, as shown in a previous study [21], including in the elderly or pediatric population [22][23], because of a different mechanism than neostigmine by directly binding and rapidly inactivating steroidal neuromuscular blockers [24].…”
Section: Discussionmentioning
confidence: 95%
“…This implies that NMB has a sedative effect by decreasing afferent input and subsequent stimulation of brain arousal centers [19][20]. Tracheal extubation time was de ned as the time between study drug administration to extubation, which was much shorter in the sugammadex group, as shown in a previous study [21], including in the elderly or pediatric population [22][23], because of a different mechanism than neostigmine by directly binding and rapidly inactivating steroidal neuromuscular blockers [24].…”
Section: Discussionmentioning
confidence: 95%
“…The previously referenced article of Gaver et al included only 18 neonates in the retrospective cohort of 968 pediatric patients who had received sugammadex. 34 Despite the limited number of neonates, the difference in the end-interval time (administration of reversal agent to OR exit time) between patients receiving sugammadex and those receiving neostigmine was greatest in the neonatal group as patients receiving sugammadex left the OR on an average of 11.94 minutes faster. No adverse effects and no difficulties with reversal of neuromuscular blockade were noted in neonates.…”
Section: Renal Transplant Recipients and Renal Failure Patientsmentioning
confidence: 99%
“…Other large, open label series, and retrospective reviews have reported the successful use of sugammadex to reverse perioperative neuromuscular blockade in various clinical scenarios in the pediatric-aged patient. [32][33][34][35] The first of these, published in the Russian literature, outlined the use of sugammadex in a cohort of 42 pediatric patients (2-17 years of age) undergoing surgery for oncologic conditions. 32 Retrospective experience has also demonstrated the efficacy of sugammadex as a component of a "fast track" anesthesia protocol to reverse neuromuscular blockade in a cohort of 14 pediatric patients following surgery for congenital heart disease using cardiopulmonary bypass.…”
Section: Open Label Pediatric Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pediatric population, evidence showed a more rapid reversal to a train-of-four of 0.9 with sugammadex compared with neostigmine without significant adverse events. [11][12][13][14][15][16] The rapid reversal of NMB achieved by sugammadex makes it an attractive alternative to neostigmine. However, there is a lack of published data regarding more functional endpoints, such as adequate ventilation, comparing the 2 medications.…”
mentioning
confidence: 99%